Allelopathic effects of herbicide-treated bracken (Pteridium esculentum Forst, f. Cockayne) fronds on white clover and perennial ryegrass - Loresco, M. M. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2006)
Controlled environment studies were carried out to determine the possible allelopathic effects of the application of mulch and extracts from fronds of bracken (Pteridium esculentum Forst, f. Cockayne) gathered from the field 3 mo after the application of growth promoters (ethephon and ammonium sulphate) and the sulfonylurea herbicide metsulfuron-methyl, alone or as combined treatments) in white clover (Trifolium repens) and perennial ryegrass (Lolium perenne). The application of bracken mulch showed no significant effects on the growth and development of the two test plants during the 12-wk growing period. Some bracken extracts inhibited root and shoot growth of white clover. Root and shoot elongation of perennial ryegrass was not affected in the glasshouse experiment but significant effects were noted in the growth cabinet; toxicity response was possibly induced because of poor seed vigor. The herbicide appeared to promote the allelopathic potential of bracken fronds. Supplementing the herbicide with growth regulators reduced allelopathic effects of fronds on the two forage species.